ANALISIS KINERJA PT BANK BNI SYARIAH SESUDAH PEMISAHAN (SPIN OFF) DARI PT BANK BNI (PERSERO)TBK - Achmad Chotib (Universitas Mercu Buana, 2016)
Islamic bank has growth well in Indonesia, and improve the economic and social welfare. Stragegic decision related to establisement of Islamic Bank is spin off. There are only 2 banks in Indonesia that really spin off: PT. Bank BNI Syariah (BNI Syariah) and PT. Bank Jabar Banten Syariah (BJB Syariah). The purpose of this study was to analyze the performance of BNI Syariah before the spin-off compared with after the spin-off and to analyze the performance of BNI Syariah after the spin-off compared with the performance of BJB Syariah after the spin off. Both of the performance analysis based on CAR, NPF, NPM, ROA, ROE, and FDR. The study was conducted by using analysis Paired Sample T-Test and Independent Sample T-Test. Based on quaterly financial reporting in year 2008-2012 the result showed that the performance of BNI Syariah before and after the spin-off does not difference significantly. The comparation of BNI Syariah and BJB Syariah after spin off showed that some ratios (NPF, NPM, ROA, ROE) did not difference significantly, but for CAR and FDR, there was a significant difference